Flowability properties of binary powder mixtures containing dates powder (Pheonix dactylifera) mixed with lactose monohydrate and microcrystalline cellulose based excipients - Ahmad Hamidi, Fara Wahida; Anuar, Mohd Shamsul; Baharuddin, Azhari Samsu; P. Mohammed, Mohd Afandi; Naim, Mohd Nazli; Mohd Tahir, Suraya (Penerbit UTM Press, 2023)
Powder flow is important in powder processing industries to obtain a quality by design product and efficient manufacturing process. Poor powder flowability can cause problems especially during high speed tableting and capsule filling processes. In this study, dates powder (DP), lactose monohydrate powder, and two types of microcrystalline-based powder excipients evaluated for their flow properties as a binary mixture. Angle of repose (AoR), Hausner ratio (HR) and Carr index (CI) were used to characterize the extent of the powder cohesion. The results show that generally, as particle size increases, values of AoR generally decreases, depicting lower flowability characteristics with decreasing binary mixture particle size. However, HR and CI flowability indicators give contrasting flowability characteristics for the binary mixture containing lactose monohydrate and dates powder.